Class of 1961 Tree Planting (1961)
Written on verso: "Class of 1961 Tree Planting." It was a practice for the graduating class to plant a tree during commencement week. This palm is being planted on the Mott Gym lawn, across from the dining facilities. See also this photo http://digital.lib.calpoly.edu/rekl-4659